3-D azimuthal anisotropy structure reveals different deformation modes of the crust and upper mantle in the southeastern Tibetan Plateau - Zhang, Zhiqi; Feng, Jikun; Yao, Huajian (Frontiers in Earth Science, 2023)
The tectonic evolution and deformation process of the southeastern Tibetan Plateau has been one of the focuses of the geoscience community in recent decades. However, the crustal and mantle deformation mechanism in the southeastern Tibetan Plateau is still under debate. Seismic anisotropy inferred from surface wave tomography could provide critical insights into the deformation mechanism of the Earth’s tectonosphere. Here, we constructed a 3-D azimuthal anisotropy velocity model with Rayleigh wave phase velocity dispersion data from 132 permanent stations to analyze the deformation modes in the southeastern Tibetan Plateau. In the upper crust, the azimuthal anisotropy near the main strike-slip faults exhibits strong magnitude with fast axis subparallel to the fault strike, which is consistent with the rigid block extrusion pattern. In the mid-lower crust, two low-velocity anomalies appeared beneath the Sonpan-Ganzi Terrane and Xiaojiang Fault zone with strong azimuthal anisotropy, which may indicate ductile deformation of the weak low crust. However, the two low-velocity anomalies are separated by a high-velocity barrier with azimuthal weak anisotropy in the inner zone of the Emeishan large igneous province. In the upper mantle, the anisotropy pattern is relatively simple in the rigid Yangtze Craton and mainly represents fossil anisotropy. In the southern part, the lithosphere thinned beneath the Indochina and Cathaysia Blocks, and the anisotropy is plausibly caused by the upwelling and lateral flows of upwelling hot asthenospheric materials.